Alteplase Treatment does not Increase Brain Injury After Mechanical Middle Cerebral Artery Occlusion in the Rat. Issue 11 (November 2013) - Sutherland, Brad A; Buchan, Alastair M
Recanalization of an occluded vessel with recombinant tissue plasminogen activator is an effective strategy for treating acute ischemic stroke. Recombinant tissue plasminogen activator is administered as alteplase, a formulation containing many excipients including L-arginine, the substrate for nitric oxide production. Most studies fail to compare the effects of alteplase on brain injury to its L-arginine carrier solution. This study aimed to verify the previously reported detrimental effects of alteplase after cerebral ischemia and delineate the contribution of L-arginine. Male Wistar rats, subjected to 90 minutes of intraluminal middle cerebral artery occlusion (MCAO), were administered alteplase, the carrier solution or saline upon reperfusion. Neither alteplase nor the carrier affected cerebral blood flow (CBF) restoration throughout the first 60 minutes of reperfusion. Alteplase treatment was associated with increased mortality after MCAO. Twenty-four hours after MCAO, neurologic function and infarct volume did not differ between rats treated with alteplase, the carrier solution, or saline. Irrespective of treatment group, infarct volume was correlated with CBF during reperfusion, neuroscore, and peri-infarct depolarizations. These results suggest that alteplase treatment, independent of thrombolysis, does not cause increased ischemic injury compared with its appropriate carrier solution, supporting the continued use of alteplase in eligible ischemic stroke patients.